THE IMPACT OF ENTREPRENEURSHIP ORIENTATION AND BUSINESS STRATEGY ON COMPETITIVENESS IN IMPROVING BUSINESS PERFORMANCE - Bunga Aditi; Pitono Pitono; Alvin Fahlevi; Aulia Arief; Muller Tamba (SEAN Institute, 2023)
MSMEs have a strategic role in supporting regional economic growth. However, during this pandemic, SMEs are facing obstacles such as reduced sales, limited distribution capital, raw material problems, and reduced production. This research was conducted by analyzing. This research developed a theoretical model based on the Structural Equation Model (SEM) which was tested using Amos 1.8 as an analytical tool. Respondents from this study were 128 consumers of MSME products in Garut Regency. The results of this study indicate that Entrepreneurial Orientation has no effect on competitiveness, Business strategy has an effect on Competitiveness, Entrepreneurial orientation has no effect on business performance, Business strategy has no effect on business performance, Competitiveness has an effect on business performance. The implication of this study is an entrepreneurial orientation in handling doing business in MSMEs. Someone who dares to take risks can be defined as someone who is opportunity-oriented in the context of uncertainty in decision-making. The business strategy carried out has an impact on increasing competitiveness compared to competitors. Business actors are expected to be able to improve their business performance by continuing to build even better products by increasing marketing through digital marketing. Likewise, innovating products can increase profits from the business. The limitations of this study were due to the very short time, the researchers distributed questionnaires so that many respondents could not be interviewed in depth.